Diabetes and atrial fibrillation in hospitalized patients in the United States - Kumar, Nilay; Echouffo‐Tcheugui, Justin B. (Clinical cardiology (Mahwah, N.J.), 2021)
Background Data on the burden of atrial fibrillation (AF) associated with diabetes among hospitalized patients are scarce. We assessed the AF‐related hospitalizations trends in patients with diabetes, and compared AF outcomes in patients with diabetes to those without diabetes. Hypothesis AF‐related health outcomes differ between patient with diabetes and without diabetes. Methods Using the National Inpatient Sample (NIS) 2004–2014, we studied trends in AF hospitalization rate among diabetic patients, and compared in‐hospital case fatality rate, length of stay (LOS), cost and utilization of rhythm control therapies, and 30‐day readmission rate between patients with and without diabetes. Logistic or Cox regression models were used to assess the differences in AF outcomes by diabetes status. Results Over the study period, there were 4 325 522 AF‐related hospitalizations, of which 1 075 770 (24.9%) had a diagnosis of diabetes. There was a temporal increase in AF hospitalization rate among diabetic patients (10.4 to 14.4 per 1000 hospitalizations among patients with diabetes; +4.4% yearly change, p‐trend < .0001). Among AF patients, those with diabetes had a lower in‐hospital mortality (adjusted odds ratio [aOR]: 0.68; 95% CI: 0.65–0.72) and LOS (aOR: 0.95; 95% CI: 0.94–0.96), but no difference in costs (aOR: 0.95; 95% CI: 0.94–0.96) and a higher 30‐day rate of readmissions compared with no diabetes (aHR 1.05; 95% CI: 1.01–1.08), compared to individuals without diabetes. Conclusion AF and diabetes coexist among hospitalized patients, with rising trends over the last decade. Diabetes is associated with lower rates in‐hospital adverse AF outcomes, but a higher 30‐day readmission risk.